2021
DOI: 10.1111/jsr.13439
|View full text |Cite
|
Sign up to set email alerts
|

Nightmare content during the COVID‐19 pandemic: Influence of COVID‐related stress and sleep disruption in the United States

Abstract: Nightmares are often associated with psychiatric disorders and acute stress. This study explores how the COVID‐19 pandemic may have influenced the content of nightmares. A sample of N = 419 US adults completed online surveys about sleep and COVID‐19 experiences. Participants were asked about the degree to which they agreed with statements linking greater general stress, worse overall sleep and more middle‐of‐the‐night insomnia with the COVID‐19 pandemic. They were also asked if, during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 41 publications
(61 reference statements)
3
34
0
Order By: Relevance
“…The relationship of dream features with psychiatric symptoms and psychological well-being during the pandemic has been assessed by different studies. The most consistent results point to a relationship between different stress/post-traumatic stress measures and dream recall frequency in the general population ( Fränkl et al, 2021 , Solomonova et al, 2021 ) and COVID-19 patients ( Scarpelli et al, 2022b ), more accentuated dream-association networks ( Pesonen et al, 2020 ), and specific dream and nightmare contents ( Solomonova et al, 2021 , Kennedy et al, 2022 ). Depressive symptoms have been associated with dream frequency ( Gorgoni et al, 2021b , but see Fränkl et al, (2021) for the effect of PTSD), emotional intensity, negative emotions, vividness ( Gorgoni et al, 2021b ), frequency of specific dream contents (Solomononva et al, 2021), nightmare frequency ( Scarpelli et al, 2021a ) and themes ( Kennedy et al, 2022 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The relationship of dream features with psychiatric symptoms and psychological well-being during the pandemic has been assessed by different studies. The most consistent results point to a relationship between different stress/post-traumatic stress measures and dream recall frequency in the general population ( Fränkl et al, 2021 , Solomonova et al, 2021 ) and COVID-19 patients ( Scarpelli et al, 2022b ), more accentuated dream-association networks ( Pesonen et al, 2020 ), and specific dream and nightmare contents ( Solomonova et al, 2021 , Kennedy et al, 2022 ). Depressive symptoms have been associated with dream frequency ( Gorgoni et al, 2021b , but see Fränkl et al, (2021) for the effect of PTSD), emotional intensity, negative emotions, vividness ( Gorgoni et al, 2021b ), frequency of specific dream contents (Solomononva et al, 2021), nightmare frequency ( Scarpelli et al, 2021a ) and themes ( Kennedy et al, 2022 ).…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, it is difficult to provide a reliable characterization of dream contents during the pandemic. Despite such heterogeneity, a common observation obtained through the analysis of dream contents/themes is the pandemic-related increase or the frequent presence during the pandemic of distressing, emotionally negative contents in the oneiric activity ( Mota et al, 2020 , Musse et al, 2020 , Iorio et al, 2020 , Kennedy et al, 2022 ; Kilius net al, 2021; Sommantico et al, 2021 ; Pesonen et al, 2020 ; Solomonova et al, 2021 ; Wang et al, 2021 ; Alghamdi et al, 2022 ). The presence of explicit pandemic-related contents and themes has been revealed by several studies but results about their prevalence are not consistent ( MacKay and DeCicco, 2020 , Musse et al, 2020 , Mota et al, 2020 , Iorio et al, 2020 , Sommantico et al, 2021 , Pesonen et al, 2020 , Borghi et al, 2021 , Kennedy et al, 2022 , Solomonova et al, 2021 , Guerrero-Gomez et al, 2021 , Alghamdi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted that the pandemic had an influence on dream and nightmare contents [ 18 , 25 , 26 , 27 , 28 , 29 , 30 ]. Here, we found that, despite a substantial stability in the most frequently reported dream themes, only the frequency of specific dream contents was reduced in PL.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in different countries found pandemic-related increases in dream and nightmare recall frequency [ 17 , 18 , 19 , 20 , 21 , 22 ]. Furthermore, changes in the qualitative features of dreams [ 19 , 22 , 23 ] and pandemic-related dream contents [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ] have been described. Different factors seem to influence specific pandemic-related dream changes [ 18 , 19 , 20 , 21 , 22 , 28 , 30 , 31 , 32 ], including modifications of the sleep pattern, characteristics of daily experience, emotional status, and sociodemographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Another study analyzing the pandemic's influence on the frequency and content of nightmares found that participants who reported greater general COVID-related stress were more likely to have nightmares. Many nightmares were reported to include content related to the pandemic, such as home confinement [27].…”
Section: Discussionmentioning
confidence: 99%